Inequality of Gender Relations during the COVID-19 Pandemic: A Study of Violence against Women in Sambas, West Kalimantan - Asman Asman (Sawwa: Jurnal Studi Gender, 2021)
During the COVID-19 pandemic, the Sambas Religious Court reported 760 domestic violence cases within a year in Sambas West Kalimantan. The violence was often used to maintain and reinforce the subordination of women to men. This study aims to determine the causes of violence against women. The descriptive qualitative method with an empirical sociological approach is applied in this study. This study involves stakeholders related to violence against women in the region as participants. The findings of this study are during the COVID-19 pandemic, from 2019-2020 violence against women increases from 450 to 760 cases. The violence occurs due to challenges and limitations especially economic problems that families face as the consequences of the pandemic. This study also finds that imbalanced power relations between men and women due to a lack of awareness of gender equality become the root cause of the violence.